(untitled) (Profetik: Jurnal Komunikasi, 2017)
Dakwah activities as a communication process of delivering the teachings of Islam’s ideal has no power to change people for the better. There are many causal factors, one of them is because of propagandas that has been done tends to be cold, impersonal, and is only informative sheer, yet using less effective communication ethics. A visual cultural revolution is now growing rapidly, unfortunately its dominated by capitalists and worshipers of lust. For example, nearly all visual ads is using the interest of sensuality and lust to lure customers. On the billboards, media newspapers, magazines, television and other media, visual communication seemed to be a valuable garbage, and this is very dangerous, especially if in the consumption of children who are mentally and immature psyche. The Effects of visual "value-free" communication can damage the sense of children as the next generation, we are slowly showed on-aurast which makes Muslims become stupid. This study aims to provide a creative space to explore the lives of children for the purpose of providing religious materials in SDN Monggang Pendowoharjo Sewon Bantul. 2D animation design is expected to give a message to children that religious material is not complicated but enjoyable. And the use of cartoon animation techniques in the making is in fact, expecting the material to be delivered to children to be light for their minds and appropriate with their entertainment media which is television. This research Visual Communication Design using 2d Animation For Children is using descriptive study which is a qualitative research method that analyze the words or sentences and separate it by category for the conclusion. Qualitative research aims to explain the phenomenon in detail and in-depth data collection that focuses on quality rather than the quantity of data. The results of this study is that the creation of 2D animation is effective to be a dakwah media for children that will be made with a creative process, which produces valuable forms required by children. The value does not solely lie in verbal and visual language, but the value in principle occurs because of the structural and functional relationships as a system that blends the designer and children as the target audience. Keywords: Communication, Animation 2D, Children.